Fecal Carriage and Genetic Characterization of CTX-M-1/9/1-Producing Escherichia coli From Healthy Humans in Hangzhou, China - Chen, Jiawei; Chen, Sheng; Jiang, Yin; Zhang, Rong; Cai, Jiachang (Frontiers in Microbiology, 2021)
CTX-M-199, a novel chimeric β-lactamase which mediated resistance to sulbactam and tazobactam, was recently identified in Hangzhou, China. This study investigated the prevalence of faecal carriage of CTX-M-199 and other CTX-M-1/9/1 among healthy individuals and characterize genetic features of blaCTX-M-1/9/1-bearing mobile elements. A total of 74 Enterobacterales strains carrying various blaCTX-M-1/9/1 genes including blaCTX-M-64 (n=40), blaCTX-M-199 (n=23), blaCTX-M-123 (n=5), novel blaCTX-M-153 (n=5) and blaCTX-M-132 (n=2) were isolated from 68 out of 5,000 faecal samples of healthy adults in Hangzhou city. Phylogenetic analysis based on whole-genome sequencing (WGS) data showed that 72 blaCTX-M-1/9/1-bearing E. coli isolates were clustered into four major clades and CTX-M-199 producers can be found in three of which. Fifty-eight out of 75 blaCTX-M-1/9/1 genes were located on plasmids belonging to four Inc-types: IncI2, IncI1, IncFIB, and IncHI2. The blaCTX-M-199 genes were harbored by three of the four types of plasmids except for IncHI2. All these blaCTX-M-1/9/1 genes were carried on an ISEcp1-mediated transposition unit. In conclusion, human faecal carriage of blaCTX-M-1/9/1 was low in healthy populations of China. The ISEcp1 is commonly associated with blaCTX-M-1/9/1 and mediated its transmission on various mobile elements. Our findings provide insights into the dissemination and further development of appropriate control measures for this inhibitor-resistant β-lactamase.